Natural Crossing for Rice Variety (Oryza sativa. L) Recovery - Luluk Sulistiyo Budi (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2020)
The rice production can be reached through a good intensification pattern, in this case used of superior varieties. Superior varieties are varieties that produced from difficult activities. The research objective was to determine the success rate of natural crosses between rice varieties with jajar legowo models. The research method used a randomized block design in the fields of Banjarejo, Taman, Madiun City in the first planting season of 2019. Treatment of jajar legowo model was 2:1, the varieties used a Trisakti and rice genotype A. The test results show that real rice grains to good crossovers weight and number of grains with high variation.The results of this research will be carried out with the next testing stages, the grain characters to obtain new superior varieties. The superior characteristic that is expected is the combination of superior traits of both parents and superior varieties resulting from natural crosses can be obtained after repeated selection and evaluation so that homogeneity and yield stability are maintained